1981
DOI: 10.1021/jm00136a018
|View full text |Cite
|
Sign up to set email alerts
|

Potential anticonvulsants. 1. 5-Benzylhydantoins

Abstract: A selected group of alkoxy- and halogen-substituted 5-benzylidino- and 5-benzylhydantoins was prepared and screened for anticonvulsant activity as measured by the ability of the compound to prevent maximal electroshock and metrazol-induced threshold clonic seizures in rats. The structure-activity studies revealed 5-[3-(trifluoromethyl)benzyl]hydantoin (14) to be the most potent member of the series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 3 publications
2
34
0
1
Order By: Relevance
“…The ED50 is approx. 8 mg/kg in mice (1,2). In our hands, the ED50 is 11 mg/kg (P.T.-H. Wong and S.-F. Tan, un published).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The ED50 is approx. 8 mg/kg in mice (1,2). In our hands, the ED50 is 11 mg/kg (P.T.-H. Wong and S.-F. Tan, un published).…”
mentioning
confidence: 57%
“…In our hands, the ED50 is 11 mg/kg (P.T.-H. Wong and S.-F. Tan, un published). Vida et al (3) reported that two methyl derivatives of phenytoin, 3-methyl phenytoin (3-MP) and 1,3-dimethylpheny toin (1,, are effective against MES in mice with ED50 values of about 5 and 50 mg/kg, respectively. Peak activities for 3-MP, 1,3-DMP and phenytoin were obtained at 2-3 hr post-administration, probably because the drugs were administered by the oral route as suspensions in 10% aqueous acacia.…”
mentioning
confidence: 99%
“…IR spectra were measured on a Shimadzu IR 460 spectrometer. 1 H and 13 C NMR spectra were measured with BRUKER DRX-500 AVANCE spectrometer at 500.1 and 125.8 MHz, respectively. The mass spectra were recorded on a Finnigan-Matt 8430 mass spectrometer operating at an ionization potential of 70 eV.…”
Section: Methodsmentioning
confidence: 99%
“…The hydantoin nucleus containing an active urea moiety is responsible for a variety of biological activities such as antiarrhythmic, antihypertensive, antiviral, antineoplastic, anticonvulsant, antimycobacterial, antiulcer, anti-inflammatory agents, as well as pesticides 3 . Additionally, 2-Thiohydantoin derivatives have been identified as molecules which may interact with a wide range of applications as therapeutics [4][5][6] , as well as fungicides and herbicides 7 .…”
Section: Introductionmentioning
confidence: 99%